2004
DOI: 10.1021/nl049645d
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Chemisorption on the Thermal Conductivity of Single-Wall Carbon Nanotubes

Abstract: The thermal conductivity at 300 K of (10,10) carbon nanotubes that have been functionalized by chemical attachment of phenyl rings through covalent bonding (chemisorption) at random positions has been calculated as a function of adsorption density using classical trajectories. The system exhibits a rapid drop in thermal conductivity with chemisorption, where chemisorption to as little as 1.0% of the nanotube carbon atoms reduces the thermal conductivity by over a factor of 3. The simulation results indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
144
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(162 citation statements)
references
References 14 publications
16
144
1
1
Order By: Relevance
“…4͑a͒ and 4͑b͒ are consistent with the MD simulation results of Shiomi and Maruyama, who, also using the REBO potential, found that k z for a 1000-nm-long, 0.41 nm-diameter CNTs is higher than that for a 0.68-nm-diameter CNTs with the same length. 23 Our predicted fully diffusive thermal conductivity of 355 W/m-K for the 1.36-nm-diameter CNT is consistent with the MD simulation predictions of Padgett and Brenner, 26 who modeled the same CNT using the REBO potential and predicted a fully diffusive thermal conductivity of 350 W/m-K. We note that the thermal conductivities of graphitic materials predicted using the REBO potential are lower than those measured from experiments, which range from 2,000 to 10,000 W/m-K. 3,4,25,48 This behavior is in contrast to the Tersoff potential, 49 which tends to overestimate the thermal conductivity of graphitic materials. 5 Our predictions from anharmonic lattice dynamics calculations indicate that a fully quantum mechanical treatment of the phonon transport in our CNTs at a temperature of 298 K changes the magnitude of the fully diffusive thermal conductivity by less than 5%.…”
Section: Empty Cnt Thermal Conductivitysupporting
confidence: 82%
See 1 more Smart Citation
“…4͑a͒ and 4͑b͒ are consistent with the MD simulation results of Shiomi and Maruyama, who, also using the REBO potential, found that k z for a 1000-nm-long, 0.41 nm-diameter CNTs is higher than that for a 0.68-nm-diameter CNTs with the same length. 23 Our predicted fully diffusive thermal conductivity of 355 W/m-K for the 1.36-nm-diameter CNT is consistent with the MD simulation predictions of Padgett and Brenner, 26 who modeled the same CNT using the REBO potential and predicted a fully diffusive thermal conductivity of 350 W/m-K. We note that the thermal conductivities of graphitic materials predicted using the REBO potential are lower than those measured from experiments, which range from 2,000 to 10,000 W/m-K. 3,4,25,48 This behavior is in contrast to the Tersoff potential, 49 which tends to overestimate the thermal conductivity of graphitic materials. 5 Our predictions from anharmonic lattice dynamics calculations indicate that a fully quantum mechanical treatment of the phonon transport in our CNTs at a temperature of 298 K changes the magnitude of the fully diffusive thermal conductivity by less than 5%.…”
Section: Empty Cnt Thermal Conductivitysupporting
confidence: 82%
“…1, we define the cross-sectional area of the CNTs to be A c = db, where b͑=0.34 nm͒ is the van der Waals thickness of the CNT surface and d is the CNT diameter. 23,25,26 We fix one layer of carbon atoms at the ends of the CNT to prevent atoms from sublimating. For graphene, we define the cross-sectional area to be A c = wb, where w is the width of the sheet ͑see Fig.…”
Section: Simulation Setupmentioning
confidence: 99%
“…5a. Estimates for the thermal conductivity of CNTs vary considerably [2,[14][15][16][17]. The effect of functionalization may decrease the thermal conductivity [17].…”
Section: Analytical Modeling Resultsmentioning
confidence: 99%
“…Indeed, recent years have witnessed increasing interesting in thermal conductivity of nanotubes 8,9,10,11,12,13,14,15,16,17,18,19 , the questions raised here are still open.…”
mentioning
confidence: 99%